The Implementation of Problem Based Learning to Increase Activity and Learning Outcomes of Economics Subject in Senior High School Students - Sari, Ita Purnama; Rokhmani, Lisa (Classroom Action Research Journal (CARJO), 2019)
Education with the learning model Problem Based Learning has an important role to improve the ability of active thinking and learning outcomes so that it gets good achievements because in this economic subject one of the subjects that requires deeper understanding because in learning it requires carefulness, accuracy, and sensitivity in analyzing conditions that occur in the surrounding environment. The method in this research is classroom action research which in its research requires quantitative and qualitative data which is carried out in two cycles including 4 stages, namely planning, implementing, observing and reflecting. From the results of the implementation of the research phase, it was found that the results showed that the activeness and learning outcomes experienced an increase in criteria very well in the second cycle, the results of which could be seen in the effectiveness assessment sheet and learning outcomes.